Chess Playing Robot - Nassar, Raheeq; Roba, Younis (My University, 2017)
Chess is a very famous and common game worldwide, which needs deep thinking and high strategy techniques. Since its inception in 18th century, it has attracted a great public attention from all social and cultural classes and all over the world. The first chess-playing robot was found decades ago in its simple design and abilities and made a huge evolution in the world of artificial intelligence when it defeated the world number one chess player on a real smart chessboard. Chess playing robot has been developed by time to achieve high playing performance. The chess Playing Robot is a challenge which merge Hardware and Software resources into one moving intelligent machine. In our work we focused on improving the performance of this robot in terms of motion speed, control strategies, artificial intelligence, processing speed and cost, as there are many ways to get this system done, we searched for the shortest, cheapest and the most effective one. Our project considering a chess playing robot system with a serial robotic arm and a smart chessboard which are both connected and work synchronously and controlled by Raspberry Pi 3 and Arduino Mega as microcontrollers, the movement of the robot is decided by an artificial intelligent python code, which makes some calculations to choose the best move for the current pieces positions.